Breast reconstructive surgery: A systematic literature review of adjustable expander implant in one stage breast reconstruction - Mario, Faenza; Giuseppe, Filosa Francesco; Marcello, Molle; Maria, Antonetti Andrea; Tommaso, Pelella; Paolo, Gesuete Francesco; Elisa, Grella; Francesco, Nicoletti Giovanni (Journal of plastic, reconstructive & aesthetic surgery, 2025)
Breast reconstruction is challenging in plastic surgery due to patient satisfaction with the aesthetic result and durability of the implant. Over time, different techniques have been proposed, ranging from the use of autologous tissues to silicone implants and permanent expanders (PEs), the latter continuing to be the subject of scientific debate. The aim of this review was to assess the effectiveness of one-stage surgery breast reconstruction using PE. A search of the literature was performed using PubMed, Medline, Cochrane, Embase, and Scopus. Key words used were "Becker expander implant," "adjustable expander implant," "one stage breast reconstruction Becker expander," "breast surgery Becker expander," "Becker prothesis for breast reconstruction," "breast reconstruction using an inflatable breast implant," and "one stage immediate breast reconstruction permanent expandable implant." References from retrieved articles were examined for additional studies. Patient demographics including age, body mass index, medical comorbidities, history of smoking, and history of radiation to the breast were collected. Surgical factors including type of reconstruction, timing of reconstruction (immediate vs delayed), and type and location of PE (subglandular vs submuscular with or without acellular dermal matrix sling) were recorded. Complications and aesthetic outcomes were analyzed. Twenty-seven studies involving a total of 2807 patients and 3315 implants were selected. The complication rate of one-stage surgery with PEs was higher than that of a two-stage technique. Complications related to the filling port were fewer than those related to the implant itself. Aesthetically, reconstruction with inflatable implants appeared to be comparable to the two-stage technique, although it requires a higher number of corrective procedures. The use of PEs appears to be associated with a higher incidence of complications and the need for multiple surgical procedures to achieve an aesthetic outcome comparable to that obtained with other breast reconstruction techniques. Adjustable implants may represent the ideal prosthesis for patients with breast hypoplasia, allowing the corrective surgery to be performed at earlier age.